COMMUNITY PERCEPTIONS OF WASTE MANAGEMENT PRACTICES: A QUALITATIVE STUDY IN URBAN NEIGHBORHOODS - Nidhom, Misbahun; Nurcahyani, Dwi (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
Waste management has become one of the most pressing urban challenges in developing countries, where rapid population growth and urbanization increase the volume of household waste beyond the capacity of municipal services. This study explores community perceptions of waste management practices in selected urban neighborhoods, focusing on residents’ experiences, attitudes, and challenges in participating in waste reduction and recycling programs. Using a qualitative descriptive approach, data were collected through semi-structured interviews, focus group discussions, and field observations involving 30 residents across three neighborhoods. The findings reveal that while communities recognize the importance of proper waste management for health and environmental sustainability, barriers such as limited infrastructure, lack of consistent education, and weak enforcement of regulations hinder effective participation. Cultural norms, economic considerations, and local leadership also shape attitudes toward waste disposal practices. The study highlights the critical role of community engagement, awareness campaigns, and participatory governance in strengthening sustainable waste management. Policy implications suggest that interventions should integrate local perspectives, build trust with residents, and ensure long-term accessibility of facilities.